1, 3-Benzodioxole-based fibrate derivatives as potential hypolipidemic and hepatoprotective agents. (1st July 2021) - Xie, Yun-Dong; Xu, Yan-Hong; Liu, Ji-Ping; Wang, Bin; Shi, Yong-Heng; Wang, Wei; Wang, Xiao-Ping; Sun, Meng; Xu, Xin-Ya; Bian, Xiao-Li
Graphical abstract: Highlights: 1, 3-Benzodioxole-based Fibrate Derivatives were synthesized and evaluated. Compound 12 significantly increased the expression of PPAR-α and reduced TG, TC and LDL-C in hyperlipidemic mice. Compound 12 also showed antioxidant, anti-inflammatory and hepatoprotective effects in hyperlipidemic mice. Abstract: A series of target compounds 1, 3-benzodioxole-based fibrate derivatives were designed and synthesized. All the target compounds were preliminarily evaluated by hyperlipidemia mice induced by Triton WR-1339, in which compound 12 displayed a greater anti-hyperlipidemia activity than other compounds as well as positive drug fenofibrate (FF). 12 showed a significant reduction of plasma lipids, such as triglycerides (TG), total cholesterol (TC) and low-density lipoprotein cholesterin (LDL-C), in high fat diet (HFD) induced hyperlipidemic mice. In addition, hepatic transaminases (AST and ALT) were ameliorated after administration of 12, in particular the AST, and the histopathological examination showed that 12 improved the hepatic lipid accumulation. The expression of PPAR-α involved in lipids metabolism was up-regulated in the liver tissues of 12 -treated group. Other significant activity such as antioxidant, and anti-inflammation was confirmed and reinforced the effects of 12 as a potential hypolipidemia and hepatoprotective agent.